Worshipper Experience Management: Reshaping Community-based Communication on Religious Activities amidst the Pandemic - Rochayanti, Christina; Wiendijarti, Ida; Triwardani, Reny (RSF Conference Series: Business, Management and Social Sciences, 2021)
Aspects of religious life are inseparable in discussing the social side of the dynamics of the COVID-19 pandemic. In Indonesia, various religious activities involving mass crowds are the fastest media in spreading disease. Inevitably, religious activities in the context of this pandemic are often considered a driving factor in the transmission of COVID-19. Worship and religious activities can no longer be carried out as usual. When in the early phase of the pandemic, houses of worship were closed. However, there was a policy regarding the re-functionalization of houses of worship in new normal conditions. People have started to return to worship in houses of worship, although with varying intensities. However, religious communities have experienced behavioral changes in religious life. Worship and religious activities have shifted through live streaming and online worship meetings. Here, mass media and social media play an essential role in delivering da’wah, appeals, and religious advice in helping to deal with the pandemic. Long-distance social relations have become the new normal in religious communities. This study explores communication management in religious communities in Yogyakarta and sees how digital media mediated communication dynamics between the members. This descriptive qualitative research uses a phenomenological approach. Data were obtained by conducting in-depth interviews and focus group discussions in three different religious communities in Yogyakarta, Indonesia. The study results show the role of opinion leaders in maintaining tension in mediated communication and new habits in worship, forming solidarity and spirituality among members of religious communities.